Analisis Dugaan Korupsi Pengadaan Laptop Chromebook Kemendikbudristek Dalam Perspektif Hukum Islam - Mhd Aryhta Yanfad Sitepu; Hafiizh Raihansyah Hafiizh Raihan; Tengku Mhd Radithya Othman; Sehat Saputra Tampubolon; Rezki Alfarizi Matondang Rezki Alfarizi (Tabayyun : Journal Of Islamic Studies, 2026)
The alleged corruption in the procurement of Chromebook laptops by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) has become a significant issue in public financial governance, raising concerns not only from the perspective of positive law but also from the ethical and normative framework of Islamic law. This study aims to analyze the alleged procurement irregularities through the principles of amanah (trustworthiness), ghulul (misappropriation of public assets), and maslahah (public interest) in Islamic law. This research employs a qualitative method with a normative juridical approach based on library research, utilizing primary and secondary legal materials, scholarly literature, and relevant scientific publications. The findings indicate that the management of public assets in Islamic law is fundamentally based on the principle of amanah, which requires integrity, transparency, accountability, and responsibility in exercising public authority. Furthermore, the concept of ghulul provides an ethical framework for evaluating the misuse of public resources and abuse of authority that may undermine justice and public trust. Meanwhile, the principle of maslahah emphasizes that every public policy and budget allocation must be directed toward maximizing social welfare and preventing public harm. This study contributes to the development of contemporary Islamic legal scholarship by demonstrating that the principles of amanah, ghulul, and maslahah can serve as normative instruments for assessing public governance beyond the formal dimensions of positive law. Accordingly, strengthening ethical values rooted in Islamic law is essential for promoting transparent, accountable, and justice-oriented public financial management.